2019
DOI: 10.1002/glia.23716
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of translocator protein upregulation is selective for pro‐inflammatory polarized astrocytes and microglia

Abstract: Translocator protein (TSPO) expression is increased in activated glia, and has been used as a marker of neuroinflammation in PET imaging. However, the extent to which TSPO upregulation reflects a pro‐ or anti‐inflammatory phenotype remains unclear. Our aim was to determine whether TSPO upregulation in astrocytes and microglia/macrophages is limited to a specific inflammatory phenotype. TSPO upregulation was assessed by flow cytometry in cultured astrocytes, microglia, and macrophages stimulated with lipopolysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 50 publications
(76 reference statements)
1
73
0
Order By: Relevance
“…In view of these observations, much research has been carried out in order to track TSPO expression and ligand binding not just for uncovering the secrets of neuroinflammation but also in the hope of offering non-invasive techniques for locating them, thus providing a significant impact on the diagnosis of CNS diseases. From all the available in vitro studies up to this date, TSPO upregulation is indisputably confirmed in the M1 microglial phenotype [27,39] while enhanced TSPO expression in M2 has been less unequivocal [46]. Furthermore, it was also established that TSPO ligands 2-Cl-MGV-1 (full name: (2-(2-chlorophenyl) quinazolin-4-yl dimethylcarbamate)) and MGV-1 (full name: 2-phenylquinazolin-4-yl dimethylcarbamate) expressed anti-inflammatory effects by reducing IL-1β, IL-6, tumor necrosis factor alpha (TNF-α), and interferon gamma (IFNγ) levels in lipopolysaccharide (LPS) activated microglia [47].…”
Section: Microglia and Tspomentioning
confidence: 98%
See 1 more Smart Citation
“…In view of these observations, much research has been carried out in order to track TSPO expression and ligand binding not just for uncovering the secrets of neuroinflammation but also in the hope of offering non-invasive techniques for locating them, thus providing a significant impact on the diagnosis of CNS diseases. From all the available in vitro studies up to this date, TSPO upregulation is indisputably confirmed in the M1 microglial phenotype [27,39] while enhanced TSPO expression in M2 has been less unequivocal [46]. Furthermore, it was also established that TSPO ligands 2-Cl-MGV-1 (full name: (2-(2-chlorophenyl) quinazolin-4-yl dimethylcarbamate)) and MGV-1 (full name: 2-phenylquinazolin-4-yl dimethylcarbamate) expressed anti-inflammatory effects by reducing IL-1β, IL-6, tumor necrosis factor alpha (TNF-α), and interferon gamma (IFNγ) levels in lipopolysaccharide (LPS) activated microglia [47].…”
Section: Microglia and Tspomentioning
confidence: 98%
“…In light of these assumptions regarding astrocytes, a recent report by Pannel et al about the significantly higher TSPO expression in proinflammatory polarized cultured murine astrocytes measured by immunohistochemistry assays, together with their increased uptake of 18F-DPA-713 PET tracer, notably enhances the potential utility of TSPO imaging in neuroinflammation [39]. This study also revealed that astrocytes stimulated by the anti-inflammatory IL-4 do not share these TSPO-overexpressing features; however, the authors noted the possible differences in the phenotype of these cells to A2 astrocytes as reported by Liddelow et al [29,39]. In summary, astrocytes can not only provide additional answers to the cellular mechanisms involved in the inflammatory response in the brain but are also worthy targets for TSPO PET ligand research.…”
Section: Astrocytes and Tspomentioning
confidence: 99%
“…TSPO/PBR, an often PETimaged protein is upregulated after injury [15,16]. Recent evidence from Pannell et al (2020) demonstrated that TSPO is upregulated in astrocytes and microglia when stimulated with lipopolysaccharide (LPS), and this is re ected with an increase in PET imaging of TSPO ligand 18 F-DPA-713 [21]. In addition, they demonstrated TSPO expression was signi cantly increased in microglia after AdTNF injections [21].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence from Pannell et al (2020) demonstrated that TSPO is upregulated in astrocytes and microglia when stimulated with lipopolysaccharide (LPS), and this is re ected with an increase in PET imaging of TSPO ligand 18 F-DPA-713 [21]. In addition, they demonstrated TSPO expression was signi cantly increased in microglia after AdTNF injections [21]. These data indicate that TSPO is a good marker to target in order to observe increases of pro-in ammatory microglia in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Complicating the issue further, different TSPO antibodies have different selectivities for TSPO in different cell lines 87 . Also, TSPO immunoreactivity can present as elevated or decreased expression in astrocytes, microglial cells and vascular endothelial cells as a response to some immunological stimuli, but not necessarily others 16,87,90 . A recent study compared TSPO PET of schizophrenia patients and controls with combined peripheral and CSF measures of IL1β, IFNγ, IL-10, IL-6 and TNF-α.…”
Section: Brain Glial Cell Activity In Vivo and Interaction With Circumentioning
confidence: 99%